FINANCIAL RESTRUCTURING AND RELAXATION REGULATION IMPACT TO HOTEL COMPANY CASE STUDY : PT PUDJIADI AND SONS TBK. - Triendi Marenda, Rafqi
This research is directed to determine the financial ability of PT Pudjiadi and Sons through valuation, for the restructuring and the negative net profit of the company. The purpose of this thesis is to calculate the company's free case flow in 3 different scenarios (Base, Worst and Up/Best). This analysis uses a top-down analysis, in which an analysis of macroeconomic conditions is carried out which explains the background for determining the financial assumptions for each scenario, while industry trends are also used to assess the reasonableness of the assumptions used.